Development Higher Order Thinking Skills Instruments in Human Respiration System Material - Halimah, Nur (Bioedunis Journal, 2024)
Since the heart is one of the most vital organs in people and pumps blood, human system respiration is one of the most significant biology concepts for students to comprehend. The goal of this research is to create accurate and valid breathing equipment for humans. Research and Development (RD) using the 4D model is the methodology employed in this study. Define, Design, Develop, and Disseminate are some of the stages. Because the expert validation result of 91.25, the study's findings show that the instrument the human respiration system produced is practical to use. Because it is greater than 0.325 and the reliability is greater than 0.6, the empirical validation results indicate that there are 10 valid claims.